The social impact of a local energy transition: The case of the district of Ahrweiler in Germany - Dominik Berndt; Julian Engelbert ("All change please!": Challenges and opportunities of the energy transition, 2022)
On 10 June 2011, the district council of Ahrweiler in the north of the federal state of Rhineland-Palatinate in Germany took the decision to meet 100% of the district's electricity needs through renewable energy by 2030. Yet the share of renewable energy in the district's overall electricity consumption has barely grown since then. This major discrepancy between political will and reality gave rise to a local research project entitled 'EnAHRgie - Nachhaltige Gestaltung der Landnutzung und Energieversorgung auf kommunaler Ebene. Umsetzung für die Modellregion Kreis Ahrweiler' ('EnAHRgie - the sustainable organisation of land use and energy supply at the municipal level: implementation in the model district of Ahrweiler'), funded by the BMBF (Federal Ministry of Education and Research). At TU Dortmund University, the Department of Planning and Environmental Law of the Faculty of Spatial Planning is responsible for questions relating to planning law and public administration in the context of the project. With these issues in mind, an analysis of the status quo was completed in September 2016 and showed that, from a planning point of view, the prevailing circumstances for a local energy transition in the district of Ahrweiler have been extremely unfavourable right from the start. This applies in particular to the use of wind power, which conflicts with issues surrounding the conservation of sites, species, cultural landscapes and historic buildings and monuments. The EnAHRgie project is thus likely to face a major challenge in terms of developing a sustainable energy strategy for the area under study.
urn:nbn:de:0156-41340388; hdl:10419/250056; https://econpapers.repec.org/RePEc:zbw:arlabe:32
Keywords: 710; local energy transition; renewable energy; wind turbine; environmental and social impact; citizen action group